The use of evolutionary approaches to understand single cell genomes - Luo, Haiwei (Frontiers in Microbiology, 2015)
The vast majority of environmental bacteria and archaea remain uncultivated, yet their genome sequences are rapidly becoming available through single cell sequencing technologies. Reconstructing metabolism is one common way to make use of genome sequences of ecologically important bacteria, but molecular evolutionary analysis is another approach that, while currently underused, can reveal important insights into the function of these uncultivated microbes in nature. Because genome sequences from single cells are often incomplete, metabolic reconstruction based on genome content can be compromised. However, this problem does not necessarily impede the use of phylogenomic and population genomic approaches that are based on patterns of polymorphisms and substitutions at nucleotide and amino acid sites. These approaches explore how various evolutionary forces act to assemble genetic diversity within and between lineages. In this mini-review, I present examples illustrating the benefits of analyzing single cell genomes using evolutionary approaches.